Penyelesaian Hukum Atas Penerbitan Sertipikat yang Cacad Hukum Administratif di Kota Batam - Lu Sudirman; Tony Tony (Fakultas Hukum, Universitas Internasional Batam, 2017)
Government Regulation (PP) No. 24 of 1997 on Land Registration, retained the purpose of convening the registration of land as essentially been defined in Article 19 of the BAL, namely that land registration is the task of government was held in order to guarantee legal certainty in the land sector. The problem in this research is how the legal settlement of the issuance of certificates of land rights faulty administrative law in Batam city land office? and How is legal protection for land rights certificate holders who have disabilities administrative law ?. The research method in this paper is a normative legal research methods. Results of this study that the legal settlement of the issuance of certificates of land rights faulty administrative law in the land office of Batam city is Cancellation of Land Rights. Cancellation of land rights as stipulated in Article 106 paragraph (1) of the Regulation of the Minister of Agrarian / Head of National Land Agency 9 1999 on Procedures for Granting and Cancellation Rights and the State Land Management Rights. Legal protection for holders of certificates of land rights who have disabilities administrative law that in case of issuance of certificate of land rights who have disabilities law administrative, then one can take effort cancellation of land rights before it goes to court, if the person feels the publication no disability law administrative. Based on this, the researchers concluded that the cancellation of the certificate of land rights is the impact of the system of negative publicity.